Mental Health Literacy for Teenagers through Interactive Education in Schools - Irmayani, Irmayani; Ginting, Rosita; Bangun, Sri Melda; Samura, Jul Asdar Putra; Ginting, Luci Riani; Surya Darma (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Institut Kesehatan Medistra Lubuk Pakam, 2025)
Adolescent mental health is an important aspect in optimal growth and development, but mental health literacy among students is still low. This community service activity aims to improve students' mental health literacy through interactive education at SMA Muhammadiyah 16 Lubuk Pakam. The method used is a participatory education approach with a combination of pretest-posttest, discussion, games, and educational videos. The activity was carried out in May 2025 involving 30 grade XI students who were selected purposively. The pretest results showed that only 33% of students had a good understanding of mental health. After the intervention, there was a significant increase, with 90% of students reaching the